Collective Ministerial Responsibility in British Government: the Testing of a Convention, 2010–2019. Issue 3 (31st May 2021) - Kippin, Sean; Pyper, Robert
Abstract: The functioning of the convention of collective ministerial responsibility in British government during the period 2010–19 is assessed by examining, in turn: the convention's historical context, its operation during the period of the 2010–15 Conservative‐Liberal Democrat coalition government, and its application during 2015–19 in the extraordinary circumstances of the Brexit fissures. The key variables and causal factors which historically affected the implementation of the convention continued to have relevance in this period, during which it further evolved under the relative tensions of coalition politics and the more severe strains of fundamental policy differences on a matter of strong political salience. In spite of the stresses placed upon the convention's operation during this extraordinary period, it remains viable as a core feature of the constitution.